Economic Boundary Analysis of Echelon Utilization of Retired Power Battery Considering Replacement Cost - Wang, Yali; Ye, Ze; Wei, Wen; Wu, Yongfei; Liu, Aijun; Dai, Shuangfeng (Frontiers in Energy Research, 2022)
As a large number of new energy electric vehicles are retired, the sequential utilization of retired power batteries has become one of the important means to improve the economic benefits of batteries, but there is a problem of disunity between available capacity and cycle life. Therefore, a peak-load power distribution method based on the principle of equal life of retired power batteries was proposed, which could effectively avoid the life difference caused by the battery difference and reduce the replacement cost. At the same time, in order to give reasonable investment suggestions for the stepwise utilization of retired power batteries, three economic boundary value models, including payback period, peak-valley price difference and investment cost, were constructed based on the leveling cost. Through the simulation of a 60MW/160MWh lithium iron phosphate decommissioned battery storage power station with 50% available capacity, it can be seen that when the cycle number is 2000 and the peak-valley price difference is above 0.8 yuan /kWh, it has investment value.